Qualitative and Quantitative Analysis of Bioactive Natural Products 2018 - Marcotullio, Maria Carla (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Throughout most of history, medicinal plants and their active metabolites have represented a valuable source of compounds used to prevent and to cure several diseases. Interest in natural compounds is still high as they represent a source of novel biologically/pharmacologically active compounds. Due to their high structural diversity and complexity, they are interesting structural scaffolds that can offer promising candidates for the study of new drugs, functional foods, and food additives.Plant extracts are a highly complex mixture of compounds and qualitative and quantitative analyses are necessary to ensure their quality. Furthermore, greener methods of extraction and analysis are needed today.This book is based on articles submitted for publication in the Special Issue entitled "Qualitative and Quantitative Analysis of Bioactive Natural Products" that collected original research and reviews on these topics.